Credibility of restrictive policies and low unemployment in the Czech Republic - Ulrich Thießen (Deutsches Institut für Wirtschaftsforschung (DIW); ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 1994)
Unemployment in the Czech Republic has been relatively low since inception of transition. Potential explanatory factors are high private sector employment growth, excess wage increase taxation, cuts in unemployment benefits, labor force withdrawels and active labor market policies. This paper finds that it appears difficult to explain divergent trends of unemployment in Central and Eastern Europe with labor force withdrawels, excess wage increase taxation and differences in the effectiveness of labor market policies. Therefore, it is necessary to concentrate on high private sector employment growth. Owing to severe data limitations, credibility of restrictive macroeconomic policies is qualitatively assessed and there are indications that credibility may have affected expectations and wage formation such that real wage adjustment, investment, and savings were promoted. Perhaps not surprisingly, the effect of excess wage increase taxation appears to have been marginal whereas the curtailment of unemployment compensation appears to have contributed to increased sensitivity of wage formation to the unemployment level.
Keywords: 330